2019
DOI: 10.1002/jmri.26621
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparative diagnostic accuracy evaluation of dynamic contrast‐enhanced (DCE) vs. dynamic susceptibility contrast (DSC) MR perfusion in differentiating tumor recurrence from radiation necrosis in treated high‐grade gliomas

Abstract: Background The appearance of a new enhancing lesion after surgery and chemoradiation for high‐grade glioma (HGG) presents a common diagnostic dilemma. Histopathological analysis remains the reference standard in this situation. Purpose To prospectively compare the diagnostic accuracy of dynamic contrast‐enhanced (DCE) vs. dynamic susceptibility contrast (DSC) in differentiating tumor recurrence (TR) from radiation necrosis (RN). Study Type Prospective diagnostic accuracy study. Population In all, 98 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…This study showed that the V e value gradually increased from the Sham group to the IR4h group, indicating an expansion of the EES volume. This phenomenon is considered to be mainly related to hepatocellular necrosis and vacuolization, as demonstrated by H&E examinations 27–29 . This study showed that the degrees of change in f and V e were higher than those of other imaging parameters at 2 hours (IR1h), which implied that perfusion plays a more important role in early hepatic injury induced by IIR.…”
Section: Discussionmentioning
confidence: 58%
“…This study showed that the V e value gradually increased from the Sham group to the IR4h group, indicating an expansion of the EES volume. This phenomenon is considered to be mainly related to hepatocellular necrosis and vacuolization, as demonstrated by H&E examinations 27–29 . This study showed that the degrees of change in f and V e were higher than those of other imaging parameters at 2 hours (IR1h), which implied that perfusion plays a more important role in early hepatic injury induced by IIR.…”
Section: Discussionmentioning
confidence: 58%
“…A recent meta-analysis showed pooled sensitivities and specificities for detecting tumor recurrence in high-grade gliomas using the mean rCBV (threshold range, 0.9–2.15) and maximum rCBV (threshold range, 1.49–3.1) corresponding to 88% and 88% (95% CI: 0.81–0.94; 0.78–0.95) and 93% and 76% (95% CI: 0.86–0.98; 0.66–0.85), respectively [ 20 ]. In a head-to-head comparison between DCE and DSC for the differentiation between tumor recurrence and radiation necrosis in treated high grade gliomas, DSC perfusion showed higher diagnostic accuracy than DCE perfusion [ 24 ].…”
Section: Biological Imagingmentioning
confidence: 99%
“…Therefore, the location of the low ADC values is key. Reduced ADC in the central necrosis suggests coagulative necrosis in the context of radiation necrosis whereas reduced ADC in the solid or enhancing lesion components suggests hyper-cellularity associated to recurrent tumor [ 24 ].…”
Section: Biological Imagingmentioning
confidence: 99%
“…Because of the vascular pauperization in radiation injury lesions and consequently the small volume of gadolinium accumulating in extravascular space in affected brain areas, low K trans values are expected [57, 58] while higher K trans values are expected in tumor recurrence. However, the radiation-induced endothelial damage could lead to an increased capillary permeability in radiation necrosis with feedback of K trans values higher than expected [59].…”
Section: Imaging Features Of Hadrontherapy-related Brain Injurymentioning
confidence: 99%
“…In particular, in order to differentiate tumor recurrence and radiation necrosis in treated high-grade gliomas, Zakhari et al [59] reported that DSC-derived CBV measurement is more accurate compared with DCE-derived parameters including the permeability parameter ( K trans ). They also reported that a combination of T1 and T2 perfusion parameters showed no significant improvement in diagnostic accuracy compared with CBV.…”
Section: Imaging Features Of Hadrontherapy-related Brain Injurymentioning
confidence: 99%